Radiological changes five years after unicompartmental knee replacement. - Weale, A; Murray, D; Baines, J; Newman, J (2000)
Failure of a unicompartmental knee replacement (UKR) may be caused by progressive osteoarthritis of the knee and/or failure of the prosthesis. Limb alignment can influence both of these factors. We have examined the fate of the other compartments and measured changes in leg alignment after UKR. A total of 50 UKRs was carried out on 45 carefully selected patients between 1989 and 1992. At operation, deliberate attempts were made to avoid overcorrection of the deformity. Four patients died, one patient was lost to follow-up and two knees were revised before review which was at a minimum of five years. Standard long-leg weight-bearing anteroposterior views of the knee and skyline views of the patellofemoral joint were taken before and at eight months and five years after operation. The radiographs of the remaining 43 knees were reviewed twice by blind and randomised assessment to measure the progression of osteoarthritis within the joints. Overcorrection of the deformity in the coronal plane was avoided in all but two knees. Only one showed evidence of progression of osteoarthritis within the patellofemoral joint, and this was only identified in one of the four assessments. Deterioration in the state of the opposite tibiofemoral compartment was not seen. Varus deformity tended to recur. Recurrent varus of 2 degrees was observed between eight months and five years after operation. There was no correlation between the postoperative tibiofemoral angle and the extent of recurrent varus recorded at five years. Changes in alignment may be indicative of minor polyethylene wear or of subsidence of the tibial component. The incidence of progressive osteoarthritis within the knee was very low after UKR. Patients should be carefully selected and overcorrection of the deformity be avoided.